Sustainable Tourism Livelihood Assets in Community-Based and Capital-Based Tourism in Labuan Bajo - Wibowo DC, Yesi Pandu Pratama; Khadijah, Siti Adelita Raif; Hamdani, Ayu Rakhmi Tiara; Ayu, Jati Paras; Rachmawati, Dewi (Graduate School, Universitas Brawijaya, 2025)
This study examines sustainable livelihood assets within community-based and capital-based tourism in Labuan Bajo, focusing on Sanggar Budaya Kope Oles Todo Kongkol and the Phinisi Rafida liveaboard ship. The objective of this research is to compare the availability, quality, ownership, and access to livelihood capitals across the two tourism models using the Sustainable Livelihood Framework for Tourism (SLFT). Employing a qualitative descriptive methodology, the research involved 3 informants selected through purposive sampling, including community leaders, government representatives, tourism workers, and industry practitioners. Data collection involved observations, semi-structured interviews, and documentation, engaging stakeholders such as community leaders, government representatives, and industry practitioners. The findings reveal that community-based tourism relies significantly on cultural and natural assets but faces challenges in financial distribution, infrastructure development, and cultural preservation, particularly among younger generations. Conversely, capital-based tourism requires substantial financial and operational investments, prioritizing skilled human resources, robust infrastructure, and collaborative social networks to ensure operational sustainability. Policy recommendations emphasize establishing formal tourism groups (Pokdarwis), developing programs to safeguard cultural practices, improving environmentally responsible infrastructure planning, implementing comprehensive risk management systems, and enhancing workforce training. The study underscores the necessity for integrated and strategic approaches across diverse tourism models to balance economic growth, environmental conservation, and cultural sustainability, offering critical insights for policymakers and stakeholders in sustainable tourism development. The practical implications of this study highlight the need for clearer community strategies to strengthen asset use, guidance for operators in integrating sustainable practices, targeted government interventions, and improved collaboration between tourism models to enhance livelihood security and reduce vulnerability.